Communication Strategies in Delivering Educational Messages on Song Lyrics “Lamunan” and “Lestari” - Eka Butsiawan; Roekhan Roekhan; Kusubakti Andajani (Journal of Pedagogi, 2024)
This research focuses on two songs by Wahyu F. Giri, "Lamunan" and "Lestari," which are popular on various music platforms. The study aims to explore the communication strategies used to convey educational messages in the song lyrics. Employing a pragmatic approach, the research analyzes the lyrics through observation and qualitative methods. The findings reveal that "Lamunan" delivers messages of loyalty, patience, love, and self-reflection, while "Lestari" emphasizes natural beauty, eternal love, loyalty, and tranquility. The communication strategies identified include repetition, audience recognition, factual delivery, and persuasion. These strategies enhance the songs' appeal and effectively impart educational values. Beyond their musicality, the songs teach listeners to appreciate relationships, the beauty of nature, and the pursuit of happiness. This study highlights how music can serve as a medium for education, embedding important values within engaging and emotionally resonant content, making it both enjoyable and meaningful for listeners.